Research on acceptance of child-rearing environment from the viewpoint of parent-child route selection and recognition of walking space in various urban environments in Japan. Issue 6 (2nd November 2022) - Cho, Sungeun; Nishide, Kazuhiko
ABSTRACT: The birthrate in Japan is declining rapidly, which is attributed to the lack of perspective and consideration for "child-rearing" in the architecture of cities. Therefore, to gain knowledge of the measures to support child-rearing, determining factors such as how urban space is used is essential. In this study, Japanese parents were requested to send pictures of their surrounding environment. The survey used the caption evaluation method to target naturally low-rise residential, planned residential, and mixed areas. On evaluation of the photographs, we found no regional differences in terms of safety and convenience. Despite the space created for walking, the parents actively enjoyed playing with the children. In the naturally low-rise residential areas, parents could select various routes. Conversely, the planned housing complexes did not have a wide choice of routes, limiting the play area. Therefore, a policy that incorporates this perspective is also necessary to improve the urban environment and consider the differences in each region to create an environment conducive to child-rearing.